Intergenerational social mobility and leisure-time physical activity in adulthood: a systematic review. Issue 7 (15th December 2016) - Elhakeem, Ahmed; Hardy, Rebecca; Bann, David; Caleyachetty, Rishi; Cosco, Theodore D; Hayhoe, Richard PG; Muthuri, Stella G; Wilson, Rebecca; Cooper, Rachel
Abstract : Aim: To systematically review the association between intergenerational social mobility and leisure-time physical activity (LTPA) in adulthood, in order to assess all published evidence relating to the hypothesis that adults socially mobile between childhood and adulthood will have different levels of LTPA than those in the same socioeconomic group across life. Methods: A systematic review was carried out following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were identified by searching databases (MEDLINE, Embase, PsycINFO) and reference lists. Eligible studies examined associations between any indicator of social mobility, based on at least one measure of parental socioeconomic position (SEP) and one measure of own adult SEP, and LTPA in adulthood. Results: 13 studies comprising a total of 44 000 participants from the UK, Finland, Sweden, Australia, USA and Brazil were included. Participants were aged 16–70 years and were from population-based surveys, occupational cohorts and primary care registries. Most studies (n=9) used occupational class measures to identify social mobility; education (n=4) and income (n=1) were also used. There was consistent evidence in nine of the 13 studies that stable high socioeconomic groups tended to report the highest levels of participation in LTPA and stable low socioeconomic groups the lowest. Upward and downwardly mobile groups participated in LTPA at levels between these stable groups. Conclusions: Cumulative exposure to higher SEP in childhood and adulthood was associated with higher LTPA in adulthood. Thus, a potential outcome of policies and interventions which aim to minimise exposure to socioeconomic adversity may be increased LTPA among adults. Trial registration number: CRD42016036538.